Beiträge zur Rechtsgeschichte Österreichs. Thomas Olechowski, Christoph Schmetterer (Hrg.), Band 1/2011. Testamente aus der Habsburgermonarchie: Allta - Dmitry Poldnikov (Journal on European History of Law, 2011)
The journal “Contributions to Austrian Legal History” (BRGÖ) was established by the decision of the Austrian Academy of Sciences on November 10, 2010 in order to encourage research in Austrian legal history.